Identifying the properties of epoxy composites filled with the solid phase of wastes from metal enterprises - Shestopalov, O.; Briankin, Oleksandr; Lebedev, V. V.; Troshin, Olexiy; Muradian, Arsen; Ocheretna, Valentyna; Yaremenko, Nadiia (Технологический Центр, 2019)
The article addresses the issue related to the disposal of dust from steel industry as a reinforcing filler for epoxy composites. The polymer composition of "cold welding" that has been developed and studied includes epoxy dian oligomer, amine hardener and the filler – finely dispersed waste of metals. Polyethylene polyamine was used as a hardener in order to improve heat resistance and strength characteristics. Manganese triacetate was used in order to decrease the temperature and reduce the time of curing. The possibility was established to dispose of finely dispersed metal-containing waste from metallurgical production to be used a filler for epoxy composites of cold curing. It was revealed that the optimal content of dusts from foundries in the composite is at the level of 45–60 %. At this content, there is the highest impact resistance at the level of 40–50 MPa and a softening temperature in the range of 170–190 °С. It was established that at an increase in the amount of a filler from 40 % to 70 %, the cross-linking degree increases by 88 % to 98 %, respectively. However, at the content of the filler less than 45 % or exceeding 60 %, the impact resistance of the resulting composites decreases. At the content of a filler in the composite less than 45 %, the cause of low values of impact resistance and softening temperature could be the low cross-linking degree, less than 90 %. A decrease in these properties of composites at the content of the filler exceeding 60 % could be associated with the formation of a heterogeneous structure of filler. In the compositions with the highest performance characteristics, there is an optimized content of the filler and catalyst. Using a hardener and a curing catalyst in quantities of 3–3.5 and 1.5–2 %, respectively, makes it possible to shorten curing time by up to 2 hours. In general, the resulting epoxy composites are superior in their performance to known cold-curing analogs. The dependences of impact resistance, softening temperature, and cross-linking degree on the content of waste in the composite were derived, which make it possible to calculate the optimal formulation for composites depending on the required properties.

Стаття присвячена проблемi утилiзацiї пилу металургiйної промисловостi як армуючого наповнювача епоксидних композитiв. Розроблена i дослiджена полiмерна композицiя "холодної зварки", що включає епоксидний дiановий олiгомер, амiнний затверджувач i наповнювач – дрiбнодисперснi вiдходи металiв. З метою пiдвищення теплостiйкостi i мiцнiстних характеристик в якостi затверджувача використовувався полiетиленполамiн. Для зниження температури i скорочення часу затвердiння в якостi прискорювача використовувався триацетат марганцю. Встановлена можливiсть утилiзацiї дрiбнодисперсних металовмiсних вiдходiв металургiйних виробництв в якостi наповнювача епоксидних композитiв холодного затвердiння. Виявлено, що оптимальний вмiст пилу ливарних виробництв в композитi знаходиться на рiвнi 45–60 %. При цьому вмiстi спостерiгається найвища ударна мiцнiсть на рiвнi 40–50 МПа i температура розм'якшення в iнтервалi 170–190 oС. Встановлено, що iз збiльшенням кiлькостi наповнювача вiд 40 % до 70 % ступiнь зшивання зростає вiд 88 % до 98 % вiдповiдно. Проте, при вмiстi наповнювача менше 45 % або бiльше 60 % знижується ударна мiцнiсть одержаних композитiв. Застосування затверджувача i прискорювача затвердiння в кiлькостях 3–3,5 i 1,5–2 % вiдповiдно дозволяє знизити час затвердiння до 2 годин. При вмiстi наповнювача в композитi менше 45 % причиною низьких значень ударної мiцностi i температури розм'якшення може бути низький ступiнь зшивання менше 90 %. Зниження вказаних властивостей композитiв при вмiстi наповнювача бiльше 60 % може бути пов'язано з утворенням неоднорiдної структури наповнювача. У композицiях з найвищими експлуатацiйними характеристиками спостерiгається оптимiзований вмiст наповнювача i прискорювача. В цiлому, одержанi епоксиднi композити за своїми експлуатацiйними характеристиками перевершують вiдомi аналоги холодного затвердiння. Встановленi залежностi ударної мiцностi, температури розм'якшення i ступеня зшивання вiд вмiсту вiдходiв в композитi, що дозволяють розраховувати оптимальний склад композитiв залежно вiд необхiдних властивостей.
Виявлення властивостей епоксидних композитів при наповненні твердою фазою відходів металевих підприємств
Keywords: cold curing epoxy composite; metallurgical dust; impact resistance; cross-linking degree; епоксидний композит холодного затвердiння; пил металургiйних виробництв; ударна мiцнiсть; ступiнь зшивання